Bismuth vanadate: A versatile heterogeneous catalyst for photocatalytic functionalization of C(sp2)–H bonds - Zeng, Fan-Lin; Zhu, Hu-Lin; Wang, Ru-Nan; Yuan, Xiao-Ya; Sun, Kai; Qu, Ling-Bo; Chen, Xiao-Lan; Yu, Bing (Chinese journal of catalysis, 2023)
Bismuth vanadate hydrothermally synthesized at 180 °C and then calcined (BiVO4-180) is a versatile and stable heterogeneous photocatalyst for the functionalization of diverse C(sp2)–H bonds under ambient visible-light conditions, with a series of functionalized compounds, including tetrahydroquinoline-succinimide-fused heterocycles, tetrahydroquinolines, 3-(p-(N,N-dimethyl)ben- zyl)indoles, α-aryl α-amino acid esters, and thiocyanated/vulcanized/selenated (hetero)aromatics, synthesized in good yields (79 examples, including modified drugs and dipeptide esters). BiVO4 photocatalysts are advantageous because they are recyclable, inexpensive, air-tolerant, and highly efficient, which are typical characteristics required to overcome the shortcomings of homogeneous photocatalysts. The bismuth vanadate synthesized by the hydrothermal/calcination combined method at 180 °C (BiVO4-180) is demonstrated to be a versatile heterogeneous photocatalyst for diverse C(sp2)–H functionalization reactions under visible light irradiation at ambient conditions.